Outcomes following percutaneous treatment of biliary stones. Issue 8 (August 2019) - Cappelli, Alberta; Mosconi, Cristina; Cucchetti, Alessandro; Pettinari, Irene; Andreone, Andrea; Zanardi, Sara; Modestino, Francesco; De Benedittis, Caterina; Serenari, Matteo; Golfieri, Rita
Abstract: Background: The percutaneous approach (PA) for management of biliary stones (BS) with or without an underlying biliary stenosis is an option for patients in whom an endoscopic approach (EA) is not possible. The aim of this study was to evaluate the efficacy of a PA in patients with BS unsuitable for an EA. Methods: A retrospective review of a database was performed. Inclusion criteria included patients with benign disease, BS who had undergone a PA. The outcomes were technical success rate, short (≤90 days) and long-term (>90 days) efficacy and safety. Results: A total of 91 patients enrolled were divided into those with (n = 38) or without (n = 53) a biliary stenosis. A median of 5 (IQR:3–7) treatments/patient were performed. During a median follow-up of 23 months (IQR:3–52), the median time free from recurrence was 21 months (CI:14–29). In the long term, the PA was most efficacious in those patients without a biliary stenosis with long term success in 68% of patients as compared to 36% of patients with a biliary stenosis (p = 0.003). Conclusion: A PA is an effective procedure with high initial success rate, however the coexistence of stenosis affects long-term efficacy, especially in patients with chronic biliary disease.